1987
DOI: 10.1007/bf02388238
|View full text |Cite
|
Sign up to set email alerts
|

Vascular compromise in chronic volvulus with midgut malrotation

Abstract: Three cases of chronic volvulus of the small bowel in midgut malrotation are presented, all of whom manifested similar angiographic findings: proximal occlusion of the superior mesenteric artery and vein and development of collateral vessels. These findings may indicate the pathophysiology of chronic volvulus in midgut malrotation; the volvulus is progressive and eventually results in the twisting of the mesenteric root itself, but because of its chronic nature collateral circulation develops, eliminating bowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 8 publications
2
15
0
2
Order By: Relevance
“…He postulates that this represents failure of counter clockwise travel of the SMV around the SMA which should have occurred during normal embryologic bowel rotation [12]. Mori and his coauthors later confirmed the CT finding of an abnormal SMA/SMV relationship [13].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…He postulates that this represents failure of counter clockwise travel of the SMV around the SMA which should have occurred during normal embryologic bowel rotation [12]. Mori and his coauthors later confirmed the CT finding of an abnormal SMA/SMV relationship [13].…”
Section: Discussionmentioning
confidence: 92%
“…More recently, sonographic description of a midline abdominal mass with whirling sonolucent layers was thought to represent the volvulized bowel loops with dilated mesenteric collateral vessels [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports of its effect on arterial blood flow during emergency surgery, demonstrated by angiographic images. [10][11][12] However, to our knowledge, there have been no reports of abnormal findings on venography or portography. When the mesentery is twisted severely enough to reduce mesenteric venous return, this can result in acute hypoperfusion of the portal vein.…”
Section: Discussionmentioning
confidence: 69%
“…In another report, 9 the authors proposed that small bowel diverticula were an independent risk factor for small bowel volvulus. In addition, Mori et al 10 discussed the concept that volvulus may be chronic and lead to vascular compromise. Although the diverticulum can be evaluated in the portal venous phase, it is easy to recognize the SMA, the location of the small bowel volvulus, and the diverticulum on MSCTA reformatted images.…”
Section: Discussionmentioning
confidence: 98%